Pusat Kajian Islam Melayu: Studi Peran Masjid Sultan Riau Masa Lalu - Ali Fahrudin (Jurnal Lektur Keagamaan, 2013)
Raja Ali Haji is one of the prominent Sultan of the Malay Riau-Lingga Sultanate.  Emperor Mosque was one of legacy of the Malay Riau-Lingga Empire which still stand firm and become the coat of arms of the Malay’s Empire in the past. This Mosque was built on the first year after King Abdurrahman crowned as The Young Lords/Yang Dipertuan Muda (YDM), Prime Minister level, who rule in the year of 1832 M- 1844 M. The feature of this Mosque among others: first, when other mosque was made from woods at the time, this mosque is already using stones and sands with egg white adhesive. Second, it has a beautiful architecture. The minaret following the Turkish Mosque pencil-shaped model, while the dome was unique it has rectangular and hexagon shape, which previously net exist in other mosques. In this mosque there are ancient manuscript, books and few manuscripts of the scholars and the Young Lords of Riau Lingga’s Empire. This study tend to elaborate the main vocal point of mosque architecture also to prove that the mosque become the study center of Moslem scholar at the time. This mosque has become the identity and symbol of the triumph of the Malay Sultanate in the past. Keywords: Sultan Mosque, Islamic Studies